Hasil Tangkapan Utama dan Tangkapan Sampingan Bagan Rambo di Perairan Teluk Lasolo Kabupaten Konawe Utara - Chaidir, Zul; Sara, La; Alimina, Naslina (JSIPi (Jurnal Sains dan Inovasi Perikanan) (Journal of Fishery Science and Innovation), 2019)
The aim of this study was analyze the main catch and by catch of bagan rambo in Lasolo Bay of Konawe Utara regency. This study was done about 2 months (on January–February) 2019 by survey method. The taking of fish samples was carried out as many as 30 trips using bagan rambo by the sampling method was stratified random sampling. All samples obtained were separated by type then measurements of the length and weight of each species were caught. The composition of the overall catch species as many as 37.881 individuals consisted of 50 species, each of 46 species of fish from 24 families and 2 groups of non fish each of 3 species of molluscs and 1 species of crustaceans. The main catch was dominate by anchovy (Stolephorus commersoni) as much as 73.83%, by catch useable as much as 26.13% consisting of 45 species, and by catch discarded as much as 0.026% consisting of 3 pufferfish species (Tetraodon sp.).Key words: catch composition, main catch, by catch, bagan rambo